Pikel Jahe (Zingiber officinalle Rosc) Diproduksi Dengan Konsentrasi Gula Dan Garam Berbeda - Yodiman Ndruru (BiSTeK Pertanian, 2021)
Ginger (Zingiber officinale Rosc.) is an important commodity in medicinal plant entrepreneurs in Indonesia as well as processed food ingredients such as ginger pikel which is one of the preserved ginger which is processed by a fermentation process. This product is obtained from the fermentation of lactic acid bacteria found on the surface of ginger rhizome and its growth is stimulated by a solution of sugar and salt (NaCl). Lactic acid bacteria (LAB) are gram-positive bacteria that do not have cytochromes, prefer anaerobic conditions, are acid-fast and are fermentative. The selected ginger pickles were fermented ginger with a concentration of 2% granulated sugar and 10% salt (NaCl) for 7 days with a pH value of 4.57, 0.52% total acid and TPC BAL 4.63 CFU/ml x 106 . Based on the results of analysis with 16SrRNA and calculation of kinship or similarity of Lactic Acid Bacteria with phylogenic trees, it was identified the types of Lactobacillus plantarum strain BM4 and Lactobacillus sp. 20(2010).